Peran Keluarga Terhadap Kepatuhan Berobat Pada Pasien Penderita TB Paru di Wilayah Kerja Puskesmas Dolo - Jurana Jurana (Biocelebes, 2008)
Research about The Effect of the Family Knowledge on the Obedient of Lung Tuberculosis Patient to Running Their Medicine Periodically. Purposive sampling method was used with 20 respondences. Result of research showed that 60% respondence have a good knowledge meanwhile 40% have less knowledge. Fifty five percent was obedient with their medicine meanwhile 45% was not obedient. Key words: Obedient, Medicine, Lung Tuberculosis.